PERBAIKAN KUALITAS CITRA DENGAN KOMBINASI METODE CONTRAST STRETCHING DAN METODE KONVOLUSI - Dimas Prasetya; Yuyun Dwi Lestari; Arief Budiman (Universitas Harapan Medan, 2020)
The use of digital images is increasing because of the advantages possessed by digital images, the lighting quality in digital images that are too dark or too bright. Where this noise is usually obtained from the image digitization process. Noise in digital image processing is a disturbance caused by deviating digital data received by the recipient of image data. The elimination of noise in the image is one of the most important parts in image processing. In the process, the images is on. The input is converted into 3x3 matrix then the process uses the contrast streching method for fix the noise from the image. In this study using the Contrast Stretching method and the Convolution method so that the objects and backgrounds in an image can be recognized more clearly